‘Prototipo de vivienda rural sostenible y productiva para la vereda alto piravante, municipio de Campoalegre, Huila’’ (2022)
In the village of Alto Piravante there are some problems focused on the lack of housing in a decentralized occupation model, therefore, these houses are not formally built, they do not have adequate habitability conditions in terms of materiality, spaces, ventilation and lighting, among others From the application of a methodology with a qualitative approach, a field work will b carried out, based on a compilation of information, not only documentary, but also with an approach to the community, where it will be tried to make an evaluation of the sustainability indicators and of the habitability conditions in the houses under stu dy. Therefore, a proposal will be developed related to improving the conditions of rural housing according to the e indicators of sustainability and habitability, taking into account the productive activities of the community.